2015
DOI: 10.1158/1078-0432.ccr-14-0817
|View full text |Cite
|
Sign up to set email alerts
|

Revised Risk Estimation and Treatment Stratification of Low- and Intermediate-Risk Neuroblastoma Patients by Integrating Clinical and Molecular Prognostic Markers

Abstract: Purpose: To optimize neuroblastoma treatment stratification, we aimed at developing a novel risk estimation system by integrating gene expression-based classification and established prognostic markers.Experimental Design: Gene expression profiles were generated from 709 neuroblastoma specimens using customized 4 Â 44 K microarrays. Classification models were built using 75 tumors with contrasting courses of disease. Validation was performed in an independent test set (n ¼ 634) by Kaplan-Meier estimates and Co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
80
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 76 publications
(83 citation statements)
references
References 34 publications
2
80
1
Order By: Relevance
“…Additionally, we successfully validated the prognostic power of these seven indexes using the expression profiles of 243 patients with newly diagnosed HR-NB 48, 49 (P < 0.05, hazard ratio >1.5, Table 2). In contrast, MYCN-amplification only moderately stratified the event-free survival in these two cohorts (P = 0.008 and 0.025, Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, we successfully validated the prognostic power of these seven indexes using the expression profiles of 243 patients with newly diagnosed HR-NB 48, 49 (P < 0.05, hazard ratio >1.5, Table 2). In contrast, MYCN-amplification only moderately stratified the event-free survival in these two cohorts (P = 0.008 and 0.025, Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Roniciclib (BAY 1000394) is a novel oral cytotoxic agent against cell-cycle and transcriptional cyclin-dependent kinases ( CDKs ) 42,43,48 . Roniciclib is currently in Phase II clinical development as a first-line therapy in combination with chemotherapy for extensive small cell lung cancer.…”
Section: Resultsmentioning
confidence: 99%
“…Our analyses showed that the associations between candidate genes and survival could not be observed by chance alone ( P = 0.039 and P = 0.0087 for Cohorts I and 2, respectively). Second, we analyzed transcriptome data from a third independent cohort (Cohort 3), consisting of 233 neuroblastoma patients extracted from the larger group in E-MTAB-1781 who were not included in Patient Cohort 1 [19]. This cohort included patients with stage 1 ( n = 41), stage 2 ( n = 40), stage 3 ( n = 22), stage 4 ( n = 111), and stage 4S ( n = 19) tumors.…”
Section: Resultsmentioning
confidence: 99%
“…Patient-specific simulations of JNK signaling were performed using three existing independent patient cohorts (55 JNK inhibitor II (SP600125) was from Merck and JNK Inhibitor VIII was from Cayman Chemical.…”
Section: Methodsmentioning
confidence: 99%